2023
DOI: 10.1002/adbi.202200172
|View full text |Cite
|
Sign up to set email alerts
|

Gene‐Directed FtsZ Ring Assembly Generates Constricted Liposomes with Stable Membrane Necks

Abstract: vesicles. With a limited number of division factors compared to eukaryotes, the Escherichia coli divisome has been at the center of numerous efforts attempting to split liposomes. [5][6][7][8][9][10][11][12] In vivo, a contractile ring composed of FtsZ, FtsA, and ZipA is formed at midcell. [13,14] FtsZ is a bacterial homologue of tubulin [15][16][17] that polymerizes into self-interacting filaments when bound to GTP. [18][19][20][21] FtsZ lacks a membrane targeting domain, and it is anchored to the cytoplasmic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…For example, the overexpression of S. pneumoniae FtsEX in E. coli also indicated an association with E.coli FtsA and could be isolated using styrene-maleic acid isolation and affinity purification as shown in Figure supplement 9C (30,31). If this holds true, it would provide a mechanism for the temporal regulation of PG cleavage at the cell division site, as FtsA and FtsZ are the key components of the constriction ring at the septum site (15,18,27,(32)(33)(34)(35)(36).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…For example, the overexpression of S. pneumoniae FtsEX in E. coli also indicated an association with E.coli FtsA and could be isolated using styrene-maleic acid isolation and affinity purification as shown in Figure supplement 9C (30,31). If this holds true, it would provide a mechanism for the temporal regulation of PG cleavage at the cell division site, as FtsA and FtsZ are the key components of the constriction ring at the septum site (15,18,27,(32)(33)(34)(35)(36).…”
Section: Discussionmentioning
confidence: 96%
“…For example, the overexpression of S. pneumoniae FtsEX in E. coli also indicated an association with E.coli FtsA and could be isolated using styrene-maleic acid isolation and affinity purification as shown in Figure supplement 9C (30, 31). If this holds true, it would provide a mechanism for the temporal regulation of PG cleavage at the cell division site, as FtsA and FtsZ are the key components of the constriction ring at the septum site (15, 18, 27, 3236). However, the identity of this density and the association of FtsEX with other Fts components for divisome formation warrant further investigation to fully elucidate the role of FtsEX in bacterial cell division.…”
Section: Discussionmentioning
confidence: 99%
“…[173] Swelling on glass beads has proven particularly effective in encapsulating IVTT systems. Recent notable results include the de novo synthesis of MinD and MinE proteins, [132] the formation of FtsA-FtsZ ring-like structures yielding constricting GUVs, [130,131] the assembly of microtubules inside GUVs, [133] and DNA-programmed membrane synthesis [134] from IVTT systems. Despite these promising results with encapsulating IVTT systems, the method has not been used for encapsulation of other biological systems.…”
Section: Encapsulation Of Complex Solute Mixtures In Physiological Bu...mentioning
confidence: 99%
“…Recent advancements in the quest for the minimal synthetic cell have been substantial, especially in critical areas such as physicochemical homeostasis, DNA replication, membrane growth, , and membrane scission. , The emerging synthetic cell will ultimately harness its own gene expression machinery to regulate these complex features. In vitro transcription-translation (in vitro transcription and translation (IVTT)) is a well-established technology for the synthesis of proteins from plasmids and linear DNA encoding for a small number of genes. Previous reports on phage genomes and large plasmids have shown that it is possible to express in the order of tens to a few hundred genes using DNA templates longer than 100 kbp. , Whereas these examples are excitingly close to a formerly postulated minimal genome (113 kbp with 151 genes), top-down experimental work on Mycoplasma established that the current minimal synthetic genome requires at least 493 genes. , From a bottom-up perspective, it is conceivable that the construction of synthetic cells requires similarly sized genomes, and these will need to be expressed in vitro.…”
Section: Introductionmentioning
confidence: 99%